2015
DOI: 10.1038/srep15076
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Opening in Behaving Non-Human Primates via Focused Ultrasound with Systemically Administered Microbubbles

Abstract: Over the past fifteen years, focused ultrasound coupled with intravenously administered microbubbles (FUS) has been proven an effective, non-invasive technique to open the blood-brain barrier (BBB) in vivo. Here we show that FUS can safely and effectively open the BBB at the basal ganglia and thalamus in alert non-human primates (NHP) while they perform a behavioral task. The BBB was successfully opened in 89% of cases at the targeted brain regions of alert NHP with an average volume of opening 28% larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 48 publications
3
64
0
Order By: Relevance
“…The closure time of the BBB after opening is not the only safety consideration for clinical translation, but our results complement existing behavioral and cognitive studies that have considered the safety of this approach in mice and primates . The time for the BBB to close after focused US is independent of the opening volume when multiple overlapping foci are used.…”
Section: Discussionsupporting
confidence: 67%
“…The closure time of the BBB after opening is not the only safety consideration for clinical translation, but our results complement existing behavioral and cognitive studies that have considered the safety of this approach in mice and primates . The time for the BBB to close after focused US is independent of the opening volume when multiple overlapping foci are used.…”
Section: Discussionsupporting
confidence: 67%
“…Early attempts in rats suggested that high‐intensity FUS can be adjusted to induce transient thermal BBB disruption without producing a lesion . Soon after this, transient BBB opening was safely achieved by low‐intensity FUS combined with an ultrasound contrast agent (microbubbles) in rabbits, rodents, and primates . The potential of FUS BBB opening for targeted delivery of therapeutic agents, chemotherapy, immunotherapy, gene therapy, viral vectors, neural stem cells, and others is being tested extensively in animal models …”
Section: Bbb Opening To Halt Nigrostriatal Neurodegenerationmentioning
confidence: 99%
“…For example, Min et al (2011) and Yang et al (2012) applied low intensity single element ultrasound to the thalamus in rat and reported changes in frontal lobe neurotransmitter concentrations though did not report data from thalamus (Min et al, 2011;Yang et al, 2012). Downs, Buch, Karakatsani, Konofagou, and Ferrera (2015) directed single element focused ultrasound at thalamus in awake behaving primate and showed ultrasound (with the addition of microbubble contrast) to safely disrupt the blood-brain barrier (Downs et al, 2015). These studies provide initial evidence of the ability of single element ultrasound to target the thalamus though these studies did not expressly study the use of ultrasound for thalamic neuromodulation.…”
Section: Introductionmentioning
confidence: 99%